Rekonstruksi Dimensi Transendental dan Sosial Generasi “Z” Masyarakat Gunung Kemukus Sragen Pasca Penutupan Lokalisasi - Muhammad Miftah (LP2M IAIN kUDUS, 2018)
Mindset is formed from the pattern of interaction among the individualswhose habit and daily behavior,then it is always repeatedso it becomes a character. The leverage level of generation Z mindset is still very vulnerable because they are influenced by environment and technological developments. They are literate and always interact with technology in life activities. The environmental urge and patterns of interaction within a community in various researches play the most vital role in human behavior change. This theory is used as the foundation of the writer to conduct research in the area of Mount Kemukus which has become a place of ritual